BURNOUTS DIDN'T HAPPEN IN INDIVIDUALS THAT HAVE A STRONG SELF EFFICACY - Mochamad Soelton ,Noermijati Noermijati , Fatchur Rohman , Mugiono , Astrid Puspaningrum , Agung Yuniarinto , Septianasari (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Human resources are an important resource that supports organizations in achieving competitive advantage. Therefore, it is important to involve employees to drive the strategic goals of the organization. Pharmaceutical companies in the era of globalization are expected to face increasingly fierce competition. Therefore, the quality of the organization must be considered. This is inseparable from the role of human resources who will be required to carry out their duties and functions properly. This research aims to examine and analyze the effect of Coping Stress, Psyches Envfironment and Self Efficacy on Turnover Intention with Burnout as an intervening variable for employees Medical Representative of Pharmaceutical Company. The object of this research is 75 employees of Pharmaceutical Company. The approach used in this research is Component or Variance Based Structural Equation Model with analysis tool Smart-PLS. The results showed coping stress that has negative and significant effects on burnout. Psyche's environment has a negative and significant effect on burnout. Self efficacy does not affect burnout. Coping stress that has negative and significant effects on turnover intention. Psyche's environment has a negative and significant effect on turnover intention. Self efficacy that has negative and significant effects on turnover intention. Burnout that has a positive and significant effect on turnover intention